The relationship between the prevalence and complexity of coronary artery disease and aortic stiffness in myocardial infarction patients without ST-segment elevation - Yildirim Arafat; Mehmet Kucukosmanoglu; Gur Mustafa (International Journal of the Cardiovascular Academy, 2020)
Background: The relationship between elastic properties of the aorta and presence of coronary artery disease (CAD) has been investigated in previous studies. However, the relationship of aortic stiffness (AS) with extent and complexity of CAD in patients with non-ST-segment elevation myocardial infarction (NSTMI) have not been evaluated in previous studies. Aims and Objectives: The aim of this study is to determine the relationship of AS with extent and complexity of CAD in patients with NSTMI. Materials and Methods: Study population includes 400 patients (265 men, 135 women, mean age 61,8 ± 10.4 years) who had coronary angiography (CAG) in our clinic between February 2013 and October 2013 with the diagnosis of NSTMI. Patients were divided into two groups according to the median SYNTAX score as SYNTAX score < 16,5 SYNTAXlow group; and SYNTAX score ≥ 16,5 SYNTAX high group. AS parameters containing pulse wave velocity (PWV) and augmentation index (AIx) were calculated using applanation tonometry. Results: PWV and AIx parameters were found to be significantly higher (P < 0.001 for each) in SYNTAX high group compared to SYNTAX low group. Also age, the frequency of HT (hypertension), HPL (hyperlipidemia) and DM (diabetes mellitus) were significantly higher (P < 0.05 for all) in SYNTAX high group. HT (β = 0.083, P = 0.048), DM (β = 0.160, P < 0.001), PWV (β = 0.520, P < 0.001), and AIx (β = 0.230, P < 0.001) were found to be independently associated with SYNTAX score in multivariate regression analysis. On the other hand, age (β = 0.255, P < 0.001), HT (β = 0.212, P < 0.001), NT-proBNP (β = 0.086, P = 0.012) and SYNTAX score (β = 0.494, P <0.001) were independently associated with PWV in multivariate regression analysis. Conclusion: SYNTAX score was found to be independently associated with increased AS in NSTMI patients. Increased AS may be thought as a predictor of extent and complexity of CAD.